Wheel-rail Dynamic Analysis under Flat-type Local Irregularity Excitation - CHEN Dilai; LIU Jianxin; DU Kaijun; LI Guopeng; WANG Yan (机车电传动)
With MATLAB software simulating the flat-type local irregularity as the external excitation of locomotive model, on the basis of the locomotive wheel-rail interaction dynamics indexed by the locomotive dynamics theory, influences of flat-type local irregularity on the locomotive wheel-rail dynamic were analyzed by using the SIMPACK multi-body dynamics simulation software. The effects of the flat-type local irregularity amplitude A, the coefficient K which’s associating with irregularity wavelength and the flat top length L on the wheel-rail dynamic performance were discussed specifically. Some important indicators, such as wheel-rail vertical force and wheel load reduction rate were given at the speed of 80km/h to 160km/h, and the risk speeds were determined. The simulation results showed that the increase of the flat-type irregularity A and the irregularity wave length coefficient K had different extents influences to the maximum of the locomotive wheelrail vertical force and the wheel load reduction rate ; but the flat top length L almost had no effect on the maximum of them.